Time investment by parents in cognitive and non-cognitive childcare activities - Mohammad Sepahvand; Roujman Shahbazian; Ranjula Bali Swain (Uppsala University, Department of Economics, 2013)
We investigate the time investment in cognitive and non-cognitive childcare activities by parents with different educational attainment. In a second step we also investigate this effect for three different child age cohorts. Past research shows that the degree of success in the labour market is highly connected to the individual's cognitive and non-cognitive skills. We compare evidence based on Multinational Time Use Study (MTUS) for five countries: France, Netherlands, Spain, United Kingdom and United States of America in order to identify any systematic pattern. The results indicate that the educational gradients for cognitive and non-cognitive childcare activities are overall positive with respect to the level of education. Furthermore, the results seem to be consistent with the technology of skill formation. They indicate a concave function between time investment and the age of the child for cognitive childcare activities and a decreasing function for non-cognitive childcare activities.
urn:nbn:se:uu:diva-200470
Keywords: I21; J13; 330; time allocation; cognitive skills; non-cognitive skills; intergenerational transmissions; human capital; technology of skill formation